The Effect of Information Quality, Quantity, Credibility, Usefulness, and Adoption on Purchase Intention of Kahf Skincare at Shopee - Rizki Ardiansyah Harahap; Ratni Prima Lita; Meuthia Meuthia (University of Merdeka Malang, 2023)
This study aims to analyze and examine the direct effect of information quality, information quantity, information credibility on information usefulness and information adoption and on purchase intention. This research is explanatory research. The sample size of this study was 216 respondents, who came from Padang City with an age range of 18-25 years and who had used shopee and knew information about Kahf skincare in Shopee e-commerce. The sampling technique in this study was non-probability with purposive sampling method. The data collection technique used a questionnaire with a Likert scale. Data analysis with Structural Equation Model with SmartPLS 4.0. The results showed that the variables of information quality, information quantity, information credibility had a positive and significant effect on information usefulness, the information usefulness variable had a positive and significant effect on information adoption and the information adoption variable had a positive and significant effect on purchase intention. Â